2023
DOI: 10.1007/s00787-023-02151-6
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of the COVID-19 pandemic on children/adolescents with ASD and their family environment: a systematic review

Abstract: The main objective of the review is to analyze the impact of the pandemic in children/teenagers with Autism spectrum disorder (ASD) and in their family environment. An electronic search was carried out in different databases (PsycInfo, Web of Science and Scopus) in order to find publications associated with the aim of this project. The search terms used were derived from the combination of the following search string: “((Pandemic OR Epidemic OR Outbreak OR COVID-19 OR Coronavirus) AND (Children OR Adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies that have investigated the impact of the COVID-19 pandemic and related containment measures on children and adolescents with autism spectrum disorders reported a significant increase in parental stress, as well as high levels of anxiety, irritability, hyperactivity, stereotypical behavior, and other behavioral problems among children and adolescents. 8 Further studies that investigated the issue of neurodevelopmental disorders showed that the COVID-19 pandemic has disproportionately and adversely affected children with attention-deficit/hyperactivity disorder (ADHD) with a recent meta-analysis pointing to a global increase in ADHD symptoms. 9 Finally, early concerns about a possible significant increase in suicidality among youth during the pandemic were followed by contradicting findings from relevant studies.…”
mentioning
confidence: 99%
“…Numerous studies that have investigated the impact of the COVID-19 pandemic and related containment measures on children and adolescents with autism spectrum disorders reported a significant increase in parental stress, as well as high levels of anxiety, irritability, hyperactivity, stereotypical behavior, and other behavioral problems among children and adolescents. 8 Further studies that investigated the issue of neurodevelopmental disorders showed that the COVID-19 pandemic has disproportionately and adversely affected children with attention-deficit/hyperactivity disorder (ADHD) with a recent meta-analysis pointing to a global increase in ADHD symptoms. 9 Finally, early concerns about a possible significant increase in suicidality among youth during the pandemic were followed by contradicting findings from relevant studies.…”
mentioning
confidence: 99%